An Implanted Magnetic Microfluidic Pump for In Vivo Bone Remodeling Applications - Chen, Ziyu (Micromachines (Basel), 2020)
Modulations of fluid flow inside the bone intramedullary cavity has been found to stimulate bone cellular activities and augment bone growth. However, study on the efficacy of the fluid modulation has been limited to external syringe pumps connected to the bone intramedullary cavity through the skin tubing. We report an implantable magnetic microfluidic pump which is suitable for in vivo studies in rodents. A compact microfluidic pump (22 mm diameter, 5 mm in thickness) with NdFeB magnets was fabricated in polydimethylsiloxane (PDMS) using a set of stainless-steel molds. An external actuator with a larger magnet was used to wirelessly actuate the magnetic microfluidic pump. The characterization of the static pressure of the microfluidic pump as a function of size of magnets was assessed. The dynamic pressure of the pump was also characterized to estimate the output of the pump. The magnetic microfluidic pump was implanted into the back of a Fischer-344 rat and connected to the intramedullary cavity of the femur using a tube. On-demand wireless magnetic operation using an actuator outside of the body was found to induce pressure modulation of up to 38 mmHg inside the femoral intramedullary cavity of the rat.